1961
DOI: 10.1139/b61-047
|View full text |Cite
|
Sign up to set email alerts
|

A CLOSED-CIRCUIT APPARATUS WITH AN INFRARED CO2 ANALYZER AND A GEIGER TUBE FOR CONTINUOUS MEASUREMENT OF CO2 EXCHANGE IN PHOTOSYNTHESIS AND RESPIRATION

Abstract: rZn apparatus is described which permits continuous monitoring of the conc e~i t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1962
1962
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…During the experiments detached twigs and leaves standing in water were sealed into a plexiglass photosynthesis chamber connected in a closed system to an infra-red C02-analyzer, as described by Lister et al (8). The volume of the whole syste-m was 0.864 liter and air was circulated through it at the rate of 0.2 liter per minute.…”
mentioning
confidence: 99%
“…During the experiments detached twigs and leaves standing in water were sealed into a plexiglass photosynthesis chamber connected in a closed system to an infra-red C02-analyzer, as described by Lister et al (8). The volume of the whole syste-m was 0.864 liter and air was circulated through it at the rate of 0.2 liter per minute.…”
mentioning
confidence: 99%
“…Technical discussions between Krotkov's group at Queen's, Vern Helson and colleagues at the new phytotron at Canada Department of Agriculture, Ottawa and Bidwell's group at Toronto led to the development of a closed-circuit apparatus with an infrared CO 2 gas analyzer and a Geiger tube system for the continuous, simultaneous measurement of 14 CO 2 and 12 CO 2 exchange in photosynthesis and respiration, as described by Lister et al (1961). (See a photograph of Lister in Figure 4b.)…”
Section: Gleb Krotkovmentioning
confidence: 99%
“…His medal address was titled: ÔThe influence of the wavelength of incident light on the path of carbon in photosynthesisÕ (Krotkov 1964). Using the closed-circuit apparatus described by Lister et al (1961), with Chlorella vulgaris cells and tobacco leaves and conditions adjusted in such a way that they absorbed the same amount of 14 CO 2 either in red light or blue light, he reported that photosynthesis in blue light as compared to red light stimulates the accumulation of 14 C in compounds connected to the Krebs cycle (aspartic, glutamic, malic and fumaric acids) and depresses the accumulation in sugars, glycine and serine. Red light stimulates the accumulation of 14 C in sugars.…”
Section: Gleb Krotkovmentioning
confidence: 99%
“…Equally important details of the light reaction involved in capturing the photosynthetically active solar radiation and converting it, via multi-steps of electron flow systems, into usable chemical energy required for CO 2 assimilation and sugar formation were also worked out by many researchers in Europe and the United States of America (Arnon 1984, Duysens 1989). Parallel to the above mentioned biochemical advances that greatly enhanced interest in photosynthetic research, plant physiologists and agronomists made efforts to study leaf photosynthetic rates of various plant species that were aided by the modern infrared CO 2 analysers (Williamson 1951) associated with leaf chamber techniques (Bosian 1955, Gaastra 1959, Egle 1960, Lister et al 1961, Hesketh 1963. The open-circuit system in which a stream of air passes into transparent chambers enclosing attached or detached leaves under illumination was employed to investigate the interrelationships between photoperiodism and CO 2 assimilation in Kalanchoe (Gregory et al 1954, Spear andThimann 1954); the effect of ecological factors on plant photosynthesis (Parker 1953, Bohning and Burnside 1956, Burnside and Bohning 1957; effects of petroleum oils on respiration (Helson and Minshall,1956); and effects of ozone on respiration and photosynthesis (Todd 1958).…”
Section: Introductionmentioning
confidence: 99%